(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Cameroon youth language. Two types of corpora are examined: Camfranglais written by its speakers and another based on transcriptions of oral corpora by researchers. It is revealed that Camfranglais written by the speakers, Cameroon youth, shows two varieties: one variety written by post-secondary school students, which includes Baccalauréat/Advanced Level holders, primary and secondary school teachers, young university lecturers, young civil servants, etc. reproduced, in all its aspects, up to grammatical inflections and graphological renderings, with original French and English languages, with a high tendency towards “Frenchification” of all non-French and English words from Cameroon source languages like Duala, Ewondo, Basaa, Mokpe, etc. Another variety of Camfranglais written by either those who did not go to school or are dropouts, or those who did not complete the entire secondary education. They lack good mastery of the source languages involved in Camfranglais, particularly French and English. This study shows that Camfranglais corpora written and/or transcribed by authors and speakers reveal linguistic tendencies, particularly at the levels of spelling, syntax and morphosyntax, which vary according to the level of knowledge of the source languages Camfranglais relies on.